KONSTITUSIONALITAS PESANTREN PASKA DISAHKANNYA UU 18 TAHUN 2019 - Erfandi Erfandi (Prodi Ilmu Hukum Universitas Nahdlatul Ulama Indonesia, 2020)
The constitutionality of Islamic boarding schools in Indonesia is experiencing a very long dynamic. Starting from the historical aspect of the establishment of the Islamic boarding school, the function of the pesantren to allowing the pesantren to collaborate with the world abroad. The state seems to be absent from the existence of Islamic boarding schools, although pesantren is the first education that has distinctive characteristics compared to education outside Indonesia. However, to be different, the existence of Islamic boarding schools and the recognition of syahadah as pesantren certificates were increasingly recognized after the passage of Law 18 of 2019 on Islamic boarding schools was passed by the Parliament together with the government.